(untitled) (Journal for Studies in Humanities and Social Sciences, 2017)
For a very long time, African history has suffered from Eurocentric biases so much so that the history and civilisation of this continent was understood as European activities. Historians of Africa paid scant attention to fashion and beauty of its people which could be partially known in the social science as sexuality. This is likely because it was considered an exclusive domain of anthropology and perhaps psychology. This situation has dramatically changed since the 1990s as trans-disciplinary studies have been encouraged. On the other hand, historians and social scientists of Africa have little interaction with visual images which can be used as alternative sources of historical phenomena. Photographs as one of the visual sources can be used to understand fashion and beauty in Africa, taking Kom in the Northwest of Cameroon as a case study. On the basis of this, I intend to look at pictures and how these made and remade the body at different times in the history of Kom as a form of leisure and fun. My interest is to showcase indigenous under-standing of this type of leisure which the Kom people engage with. What type of indigenous materials was used for their fashion and beauty? From the photographs, how can one understand the socio-cultural basis of sexuality? How can one read meaning into the various forms of body adornment, putting on of various objects such as ear rings and bangles to beautify the body, tattooing, scarification, and different hair styles at different periods of Kom history? I further wish to compare sexual representation in the photographs of Christians and non-Christians, educated and uneducated, members of royalty and commoners, and how this was shaped by ideology or social status. I collected these photographs from private archives in Cameroon and Europe during field work for my PhD thesis between 2008 and 2011.